Penerapan Pembelajaran Tematik Integratif untuk Meningkatkan Hasil Belajar IPAS pada Siswa Kelas IV di MI Gedanganak Kecamatan Ungaran Timur Kabupaten Semarang - Rohmatun, Siti; Ihyani, Luluk; Sarwono, Ridha (Faculty of Teacher Training and Education of Undaris, 2023)
This research was motivated by the low science learning outcomes of class IV MI Gedangk students. The purpose of this study was to improve student learning outcomes through the thematic integrative application of science and technology in class IV students of MI Gedanganak, East Ungaran District, Semarang Regency. The type of research used is classroom action research using the Kemmis and Mc Taggart models. The research was conducted from 4 to 10 January 2023 at MI Gedanganak. Data collection techniques in this study are by observation and tests. Observations are to measure teacher skills, while tests are to measure science learning outcomes with the application of integrative thematics at MI Gedanganak. Data analysis used quantitative data analysis to process learning outcomes and qualitative analysis to process teacher skills data. The results of the acquisition in cycle I obtained mastery learning in a classical manner of 52.8% with details of 19 students out of 36 students who had achieved the specified KKTP score for the IPAS subject, which was 75 with a classical 75%. The learning outcomes of the first cycle have not reached the specified indicators of success, so that the research has not been successful. In cycle II by paying attention to the reflection of cycle II, the learning process was improved. So that the science learning outcomes experienced an increase compared to cycle II, namely classical completeness was obtained which became 91.7% with details of 33 students out of 36 students. So that in cycle II it was declared successful because it met the criteria for research success with classical KKTP of 75%.Keywords: science learning outcomes, integrative thematic